2016
DOI: 10.11646/phytotaxa.270.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Solanum fernandesii (Solanaceae): A new species of ‘spiny solanum’ of the Gardneri clade from northeastern Brazil

Abstract: A new spiny species of Solanum L., member of the Gardneri clade, is described from northeastern Brazil. Solanum fernandesii is found in open disturbed areas of coastal plains (tabuleiros) in the caatinga biome of the states of Alagoas, Bahia, and Ceará, from sea level to 900 m of altitude. It is morphologically similar to S. agrarium Sendtn., a neotropical species known from hot and dry areas of Colombia, Venezuela, the Caribbean, and central-eastern Brazil. The two species differ mainly in their habit, blade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…In addition, it is worth noting that the number of species indicated for the flora of Ceará (BFG 2018; Flora do Brasil 2020 under construction) is incomplete. Recent studies linked to the "Flora of Ceará Project: knowing to conserve" have shown how much the floristic diversity of that state is underestimated, confirmed with quotes from new records (Capistrano & Loiola 2015;Tabosa et al 2016;Rocha et al 2018;Lima et al 2018Lima et al , 2020Sampaio et al 2019a) or description of new species (Loiola 2013;Souza et al 2016;Sampaio et al 2016Sampaio et al , 2019bRibeiro et al 2017).…”
Section: Introdutionmentioning
confidence: 86%
“…In addition, it is worth noting that the number of species indicated for the flora of Ceará (BFG 2018; Flora do Brasil 2020 under construction) is incomplete. Recent studies linked to the "Flora of Ceará Project: knowing to conserve" have shown how much the floristic diversity of that state is underestimated, confirmed with quotes from new records (Capistrano & Loiola 2015;Tabosa et al 2016;Rocha et al 2018;Lima et al 2018Lima et al , 2020Sampaio et al 2019a) or description of new species (Loiola 2013;Souza et al 2016;Sampaio et al 2016Sampaio et al , 2019bRibeiro et al 2017).…”
Section: Introdutionmentioning
confidence: 86%
“…Despite previous efforts focused on Heliotropiaceae in Brazil, the representatives of this family in Ceará state are poorly studied, and the data regarding the family in the state is outdated. In this context, studies related to the "Flora of Ceará: knowing to conserve" project have shown how underestimated the floristic diversity of the state, particularly, due to new records (Capistrano & Loiola 2015;Tabosa et al 2016) and new species descriptions (Loiola 2013;Sampaio et al 2016Sampaio et al , 2019Souza et al 2016;Ribeiro et al 2017;Santos et al 2020) occurring frequently.…”
Section: Introductionmentioning
confidence: 99%
“…Especificamente para o estado do Ceará, nenhum estudo recente foi desenvolvido com as espécies desta família e seus representantes raramente são citados nos levantamentos florísticos, sendo o número de espécies listadas muito reduzido (Araújo et al 2011;Loiola et al 2015). Merece destacar que os números indicados para a flora do Ceará estão desatualizados e estudos vinculados ao "Projeto Flora do Ceará: conhecer para conservar" têm mostrado o quanto a diversidade florística do estado está subestimada, com ocorrência de novos registros (Capistrano & Loiola 2015;Tabosa et al 2016) ou descrição de novas espécies (Loiola 2013;Sampaio et al 2016;Souza et al 2016;Ribeiro & Loiola 2017).…”
unclassified